2020
DOI: 10.1183/13993003.01796-2020
|View full text |Cite
|
Sign up to set email alerts
|

Rapid genomic first- and second-line drug resistance prediction from clinical Mycobacterium tuberculosis specimens using Deeplex-MycTB

Abstract: Targeted next generation sequencing using the Deeplex-MycTB assay can rapidly generate comprehensive drug resistance profiles from Mycobacterium tuberculosis complex cultures and directly from tuberculosis patient samples to guide personalized treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 17 publications
1
33
0
1
Order By: Relevance
“…Consistently, the similar mean read depths obtained on the specimens graded 1+, 2+ and 3+ from the DRC survey also suggest a limit of detection ≤1+ (corresponding to 5000–10 000 genomes·mL −1 of sample) with the DNA extraction conditions used, accounting also for the fact that the equivalent of about a tenth of the available 1–5 mL of the DRC samples was generally used for DNA extraction and testing. Further consistent with such analytical sensitivity, in a recent study using QIAamp DNA Mini kits for DNA extraction, complete Deeplex Myc-TB phenotypic predictions could be made from all 37 smear-positive (including five scanty) and two smear-negative samples, in a pilot series of 50 clinical specimens [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the similar mean read depths obtained on the specimens graded 1+, 2+ and 3+ from the DRC survey also suggest a limit of detection ≤1+ (corresponding to 5000–10 000 genomes·mL −1 of sample) with the DNA extraction conditions used, accounting also for the fact that the equivalent of about a tenth of the available 1–5 mL of the DRC samples was generally used for DNA extraction and testing. Further consistent with such analytical sensitivity, in a recent study using QIAamp DNA Mini kits for DNA extraction, complete Deeplex Myc-TB phenotypic predictions could be made from all 37 smear-positive (including five scanty) and two smear-negative samples, in a pilot series of 50 clinical specimens [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…sputum) is difficult 3 . We recently demonstrated that targeted genome sequencing using the commercially available Deeplex ® -MycTB has a high sensitivity and specificity for first- and second-line drug resistance prediction, including BDQ/CFZ resistance mutations that have been found in patients 47,57,58 . In combination with our comprehensive set of mutations that confer resistance to BDQ/CFZ, Deeplex®-MycTB and other targeted sequencing approaches allow for rapid detection of BDQ/CFZ resistance from clinical samples in few days using small portable genome sequencers such as the MinION 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA of 30 randomly selected clinical Mtbc isolates was extracted at the Kyrgyz NRL using the CTAB protocol (SOP provided in the supplement materials), photometrically checked and separated into two identical 25 µl aliquots. NRL and RCB independently prepared libraries using the Nextera XT kit following the instructions of the manufacturer and using a modified Nextera protocol, respectively 9 , 18 . Both laboratories independently performed and bioinformatically analyzed WGS of the isolates on MiSeq and NextSeq 500 (Illumina, USA), respectively.…”
Section: Methodsmentioning
confidence: 99%